Analysis of Effectiveness and Compliance Implementation of E-Tickets in Jakarta Using the Framework Cobit-2019 - Rafli Pamungkas; Muhammad Farhan; Vico Marviawan (International Journal of Computer Technology and Science, 2025)
The Electronic Traffic Law Enforcement (E-Tilang) system has been implemented in Jakarta as an innovative solution to address the increasingly complex problems of traffic law enforcement. This research aims to evaluate the effectiveness of the E-Tilang system's implementation by analyzing public compliance levels and measuring the system's maturity using the COBIT 2019 framework. The research method uses a quantitative approach with a survey of 113 Jakarta residents who have experience with the E-Tilang system. Data was collected through a structured questionnaire mapped to the five COBIT 2019 domains: Evaluate, , Plan and Organize (APO); Build, Acquire and Implement (BAI); Deliver, Service and Support (DSS); and Monitor, Evaluate and Assess (MEA)